Conflicts between Sales and Product Divisions Regarding New Product Development in a Manufacturing Company: What Are Key Factors to the Success of New Product Performance and Competitive Advantage - Chien, Tzu-Ying (2013)
In the high-technology manufacturing industry, it is realized by manufacturers that product offering can no longer be the only determinant to succeed in the severe environment. The concept of involving customer value into product performance and service delivery is further emphasized to be influential to a company’s success in new product development performance and its competitive advantage. However, in the real world, different perspectives are likely to be held by people from various backgrounds in an organization.